2012
DOI: 10.1007/s00018-012-1241-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of PPARβ/δ in the regulation of glutamatergic signaling in the hamster suprachiasmatic nucleus

Abstract: Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear receptor superfamily and function as transcription factors that regulate gene expression in numerous biological processes. Although the PPARβ/δ subtype is highly expressed in the brain, its physiological roles in neuronal function remain to be elucidated. In this study, we examined the presence of PPARβ/δ in the master circadian clock of the Syrian hamster and investigated its putative functional role in this structure. In mammals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…2, 4) is a phenomenon that has also been reported in other studies (described below) on transcript-protein expression relationships in the SCN. Peroxisome proliferator-activated receptor β/δ mRNA and protein display rhythmicity in the SCN of animals housed in LD cycles, but in DD, mRNA expression remains rhythmic whereas protein expression does not (Challet et al, 2013). Further evidence that transcript and protein rhythms can be uncoupled comes from a recent SCN proteome study that analyzed 2112 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…2, 4) is a phenomenon that has also been reported in other studies (described below) on transcript-protein expression relationships in the SCN. Peroxisome proliferator-activated receptor β/δ mRNA and protein display rhythmicity in the SCN of animals housed in LD cycles, but in DD, mRNA expression remains rhythmic whereas protein expression does not (Challet et al, 2013). Further evidence that transcript and protein rhythms can be uncoupled comes from a recent SCN proteome study that analyzed 2112 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember, however, that mRNA rhythms can be uncoupled from protein rhythms in the SCN (Challet et al, 2013; Chiang et al, 2014), suggesting that rhythms in protein may prove more informative than rhythms in mRNA levels. We recently found that the ratio of the δ subunit (contained in the GABA A -TONIC receptor) to the γ 2 subunit (contained in the GABA A -PHASIC receptor) is rhythmic in the SCN.…”
Section: Gaba Receptorsmentioning
confidence: 99%
“…Recently, Challet et al observed oscillations in PPAR β / δ expression in hamster SCN. Administration of PPAR β / δ agonist L-16504 amplified the delay phase of locomotor response induced by a light pulse [54], indicating that PPAR β / δ may play a role in circadian behavior. In another recent paper, Liu et al revealed a PPAR β / δ -dependent diurnal oscillation of de novo lipogenesis in mouse liver [55].…”
Section: Pparβ/δ and Circadian Clockmentioning
confidence: 99%